2022
DOI: 10.1007/s00420-022-01922-z
|View full text |Cite|
|
Sign up to set email alerts
|

Exposure to dust and respiratory health among Australian miners

Abstract: Purpose Occupational exposure to dust has been recognised as a significant health hazard to mine workers. This study aimed to investigate the association between exposure to inhalable (INH) and respirable (RES) dust and respiratory health among mine workers in Western Australia using an industry-wide exposure database. Methods The database comprised cross-sectional surveys conducted by mining companies for the period 2001–2012. The study population consist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Compared to the current study, the PMC (located about 5km from the tanzanite mines) will belong to the low exposure group residing > 1.5km from the mines’ waste. A study report among non-smokers coal workers (both underground and surface) in USA showed the prevalence of obstructive lung disease of 7.7% which went up to 16.4% among those with CWP [28] while another report among miners in Western Australia reported a prevalence of 6.3% [29].…”
Section: Discussionmentioning
confidence: 99%
“…Compared to the current study, the PMC (located about 5km from the tanzanite mines) will belong to the low exposure group residing > 1.5km from the mines’ waste. A study report among non-smokers coal workers (both underground and surface) in USA showed the prevalence of obstructive lung disease of 7.7% which went up to 16.4% among those with CWP [28] while another report among miners in Western Australia reported a prevalence of 6.3% [29].…”
Section: Discussionmentioning
confidence: 99%
“…Hayumbu et al ( 14 ) further concluded that the mining companies had substandard dust monitoring programs, which may increase miners’ risk of non-malignant disease. A retrospective analysis conducted in Australia by Rumchev et al ( 18 ) investigated the association between exposure to inhalable and respirable dust and respiratory health problems among mine workers between 2001 and 2012. The study found a decline in exposure to inhalable and respirable dust over the 12 years despite workers exhibiting high prevalence of phlegm and cough.…”
Section: Introductionmentioning
confidence: 99%
“…Dust refers to particles with a size of approximately 1-100 μm. Coal miners are frequently exposed to air filled with fibers and dust [5], making it one of the major threats to their health. It is well known that substantial occupational dust exposure can have adverse effects on the respiratory system.…”
Section: Introductionmentioning
confidence: 99%